2020
DOI: 10.1016/j.ajogmf.2020.100211
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic evaluation of placentas after diagnosis of maternal severe acute respiratory syndrome coronavirus 2 infection

Abstract: Background The impact of maternal severe acute respiratory syndrome coronavirus 2 infection on placental histopathology is not well known. Objective To determine if any significant placental histopathologic changes occur after the diagnosis of severe acute respiratory syndrome coronavirus 2 infection during pregnancy and whether these changes are correlated with the presence or absence of symptoms associated with the infection. Study Design A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 38 publications
5
76
0
8
Order By: Relevance
“…In a retrospective cohort investigation of the placentas from 50 pregnant women diagnosed with COVID-19 at a hospital in New York and compared with an equal number of control placentas from uninfected women, Gulerson et al [30] found that there were no statistically significant differences in the pathology findings between the two groups. All of the neonates from mothers with COVID-19 were negative for the virus by RT-PCR at 24 h of life.…”
Section: Placental Pathology From Mothers With Covid-19 In the Absencmentioning
confidence: 99%
“…In a retrospective cohort investigation of the placentas from 50 pregnant women diagnosed with COVID-19 at a hospital in New York and compared with an equal number of control placentas from uninfected women, Gulerson et al [30] found that there were no statistically significant differences in the pathology findings between the two groups. All of the neonates from mothers with COVID-19 were negative for the virus by RT-PCR at 24 h of life.…”
Section: Placental Pathology From Mothers With Covid-19 In the Absencmentioning
confidence: 99%
“…Reference lists of the included papers were also checked to identify additional relevant studies. We reviewed all articles (both peer-reviewed and preprints) with reports on placental pathology in pregnant women tested positive for SARS-CoV-2 that were published between 1 January 2020 to 10 October 2020 ( n = 29) [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Articles written in languages other than English and Mandarin were excluded.…”
Section: Introductionmentioning
confidence: 99%
“…In a case control study from Chicago of 15 placentas compared against 17,500 historical controls, a statistically significant increase in intervillous thrombi was demonstrated among COVID-19 patients [4]. Conversely, a retrospective control study in New York of 50 placentas from COVID-19 mothers compared to 50 control placentas from patients without COVID-19 showed no statistically significant differences [5]. In our patient, placental pathology was significant for excessive size for gestational age, intravascular fibrin, and infarctsigns of lower than average efficiency.…”
Section: Discussionmentioning
confidence: 87%
“…If the excessive volume of the placenta effectually led to restriction of fluid and movement of the arm, compression of the arm, and consequent ischemia, this would result in compartment syndrome as the etiology for ischemia. To date, COVID-19 maternal infection has not been found a risk factor for excessive placental size [5].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation